STRUCTURE AND PROPERTY BLENDING OF POLYDIMETHYLSILOXANE, POLYETHYLENE GLYCOL, POLYETHER SULFONE AND POLY ACRYL NITRILE MEMBRANES WITH TETRA METHYL ORTHO SILICATE AS CROSS-LINKING AGENT: Life Sciences-Chemistry - MOHSEN FARSI; AMIR HEIDARINASAB; BIZHAN HONARVAR; MEHDI ARJMAND (International Journal of Life Science and Pharma Research, 2022)
In this research for fabricated the composite membranes usage a blend of polymers that are comprised of PDMS (polydimethylsiloxane), PEG (polyethylene glycol), PES (polyether sulfone) and PAN (poly acryl nitrile) as polymers, asymmetric polyester ultra-filtration membranes, PES, PVP (polyvinyl pyrrolidone) as pore former and N,N-Dimethyl acetamide (DMAc) as solvent used for fabricated of support layer with crosslinking TMOS (tetramethyl orthosilicate) as silica Nanoparticles (crosslinking agent), ammonia as inducer ,dibutyltindilaurate as catalystand span 80 as surfactant.In the research, four kinds of the membrane including PDMS, blend of PDMS with PEG, blend of PDMS with PES and blend of PDMS with PAN are used. The structural morphology of support and active layers of the composite membranes was characterized with SEM. in this research, crosslinking temperature and crosslinking time are fixed and 65ċ and 1 hour respectively so this study focuses on the variation of crosslinking agent (TMOS)(1.5,3 ,4.4,5.8 and 7.15wt%) upon crosslinking density (), swelling degree (), %swelling by volume, density of membrane specimen ( ), volume fraction of rubber phase () and number average molecular weight between crosslink's (), is studied. It was observed that with increasing the weight of the crosslinking agent, , and increased and , %swelling by volume decreased, but changes of is erratic